Detection of circulating tumor cells from cryopreserved human sarcoma peripheral blood mononuclear cells. (10th September 2017) - Li, Heming; Meng, Qing H.; Noh, Hyangsoon; Batth, Izhar Singh; Somaiah, Neeta; Torres, Keila E.; Xia, Xueqing; Wang, Ruoyu; Li, Shulin
Abstract: Circulating tumor cells (CTCs) enter the vasculature or lymphatic system after shedding from the primary tumor. CTCs may serve as "seed" cells for tumor metastasis. The utility of CTCs in clinical applications for sarcoma is not fully investigated, partly owing to the necessity for fresh blood samples and the lack of a CTC-specific antibody. To overcome these drawbacks, we developed a technique for sarcoma CTCs capture and detection using cryopreserved peripheral blood mononuclear cells (PBMCs) and our proprietary cell-surface vimentin (CSV) antibody 84-1, which is specific to tumor cells. This technique was validated by sarcoma cell spiking assay, matched CTCs comparison between fresh and cryopreserved PBMCs, and independent tumor markers in multiple types of sarcoma patient blood samples. The reproducibility was maximized when cryopreserved PBMCs were prepared from fresh blood samples within 2 h of the blood draw. In summary, as far as we are aware, ours is the first report to capture and detect CTCs from cryopreserved PBMCs. Further validation in other types of tumor may help boost the feasibility and utility of CTC-based diagnosis in a centralized laboratory. Highlights: Cell-surface vimentin (CSV) is a specific marker to capture CTCs from patient cryopreserved PBMCs across sarcoma tumor types. The novel technology is validated to specifically detect and isolate sarcoma CTCs from cryopreserved PBMCs. This technique allows for the wide use of CTC-based diagnosis and treatment in clinical settings for sarcoma patients.